Antidiarrheal activity and acute oral toxicity of Mentha longifolia L. essential oil - Ghader Jalilzadeh-Amin; Massoud Maham (Mashhad University of Medical Sciences, 2015)
Objectives: Mentha longifolia L. (Lamiaceae) is an annual herb that is used in the Iranian traditional medicine for treating stomach and intestinal disorders. The purpose of this study was to determine the protective effect of M. longifolia on experimental diarrhea in a rat model. Materials and Methods: The antidiarrheal activity of essential oil of M. longifolia (20-80 mg/kg) was investigated against castor oil-induced diarrhea in rats using loperamide as the standard reference drug. In acute toxicity evaluation, rats were orally administrated with single dose of EOML at doses ranging from 10 to 1000 mg/kg. Results: EOML caused a significant (p